The antimicrobial effect of flax seed on pseudomonas aeruginosa - Mohamed Yusoff, Nurul Fatihah; Mustafa Al-Ahmad, Basma Ezzat; Subramaniam, Pram Kumar; Mustafa, Nazih Shaban; Kashmola, Muhanad Ali Hamdon; Mokhtar@Makhtar, Khairani Idah; Darnis, Deny Susanti (2019)
Flaxseed comes from the flax plant (Linum usitatissimum), which has been cultivated for domestic use since prehistoric times. Pseudomonas aeruginosa is a Gram-negative bacterium has the ability to survive in adverse environments and develop multiple antibiotic resistance mechanisms. This study aims to evaluate the susceptibility of Pseudomonas aeruginosa (P. aeruginosa) In-vitro to the ethanolic extract obtained from flax seed. This is a laboratory experimental in vitro study using P. aeruginosa cultured in nutrient agar. The pathogen then was inoculated in nutrient based broth and incubated for 24hours. Flaxseed extract efficacy was tested by measurement of the zone of inhibition. The result of the extracts antimicrobial activities were compared with streptomycin as positive control and DMSO as negative control. The statistical analysis was done by using GraphPad PRISM version 6. There is positive antibacterial effects of flaxseed extract against Pseudomonas aeruginosa and it was comparable in efficacy to that of Streptomycin. This study concludes that flaxseed extract can help in inhibiting Pseudomonas aeruginosa activity. The implication of this result will be useful in propagating the use of natural based product as therapeutic drug against the chemical synthetic products. The results of the present study scientifically validate the inhibitory capacity of Linum usitatissimum as antibiotic against one of the most resistant pathogens and contribute towards the development of new treatment options based on natural products.